P110 activation protein is strongly expressed in intestinal fibrosis in inflammatory bowel disease patients. (30th January 2023) - Lartey, D; van Roest, M; Verhoeff, J; Grootjans, J; Buskens, C; van der Bilt, J; Wildenberg, M; D'Haens, G; Löwenberg, M
Abstract: Background: Intestinal fibrosis is a common complication of inflammatory bowel disease (IBD) with limited diagnostic modalities to detect and determine the degree of fibrosis. Fibroblast activation protein alpha (FAP) is a protein with both dipeptidyl peptidase and endopeptidase properties which is virtually absent in healthy tissues and has increased expression in chronic inflammatory and fibrotic diseases. In this study, we investigated the presence of FAP in intestinal fibrosis caused by Crohn's disease (CD) and ulcerative colitis (UC). Methods: For this study, transmural surgical resection specimens were retrieved from the Tytgat institute IBD biobank located at Amsterdam University Medical Center. IBD patients undergoing an ileocecal resection for stricturing CD or a subtotal colectomy for therapy-refractory disease, and patients undergoing a right-sided hemicolectomy or ileocecal resection for dysplasia or non-metastasized colorectal cancer (CRC), were included. All patients had an established diagnosis of (CD, UC, dysplasia or CRC) by previous endoscopy and biopsies and had provided informed consent prior to surgery. FAP protein and gene expression levels were determined using immunohistochemistry staining and quantitative polymerase chain reaction (qPCR). Mass cytometry was used to identify FAP–expressing cells. Results: In total, 59 ileal and 35 colonic samples were stained and quantified to asses FAP expression (figure 1). A 1.7-fold and 1.9-fold increase of FAP protein expression was seen in inflamed (mean 22.3, p=0.0069); and stenotic (mean 25.5 p=0.0002) CD ileum compared to healthy non-IBD tissue (mean 13.1). Inflamed UC colon (mean 26.8, p = 0.0406) showed a 1.4-fold increase compared to healthy colon (mean 19.2). For the gene expression, 66 ileal and 42 colonic samples were processed and used for qPCR analysis. A 5-fold and 6.4-fold increase of FAP was found in inflamed (mean 0.011, p=0.0475) and stenotic (mean 0.014, p=0.0042) CD ileum, and a 1.7-fold increase was seen in inflamed UC colon (mean 0.278, p=0.0195) compared to controls (means: ileum 0.002; colon 0.165). Conclusion: This is the first study reporting the potential of FAP as a fibrotic biomarker not only in stricturing CD, but also in therapy-refractory UC. Significantly increased FAP protein and gene expression is found in inflamed and stenotic ileum in CD and inflamed colon in UC. Additionally, CD90+GP38+ cells have been identified as the most present FAP expressing cells.